Cash Management Practices and Financial Stability Among Pawnshops in General Santos City: A Basis for Policy Intervention to Improve Operational Efficiency - Villota, Cherry Mae M.; Salise, Kerby P. (International Journal of Research in Interdisciplinary Studies, 2025)
Cash management is vitally important as it is the key factor to any successful business. The purpose of this study was to determine the cash management practices and financial stability as measured by the sound cash position among pawnshops in General Santos City. The study used a quantitative descriptive-correlational approach that involved fifty (50) respondents from different pawnshops. Quantitative data was analyzed using descriptive statistics, Spearman correlation, and Analysis of Variance (ANOVA). Results revealed that Pawnshops in General Santos City constantly employed cash management practices and maintained a sound cash position. Among the four key areas assessed, Preventing Fraud and Internal Control received the highest mean, which highlights a strong emphasis on safeguarding transactions and daily operations. Cash Flow Monitoring is also regularly practiced while Liquidity Management is effectively applied, findings suggest that strategies for maintaining adequate cash reserves may require further improvement. On the other hand, Budget Management received the lowest mean, indicating that although budgeting practices existed, they are less rigorously practiced compared to other areas. The study concluded that cash management practices have a significant relationship to financial stability. This suggests that an increase in cash management practices also increases financial stability. However, among the moderating variables, the number of employees significantly moderates the relationship between cash management and financial stability, where pawnshops with only 1–2 employees show a slightly weaker positive impact. The study provides recommendations for strengthening cash management strategies to enhance financial stability and ensure the long-term sustainability of pawnshops in General Santos City.